Réponses

Meilleure réponse !
2014-09-23T16:21:14+02:00
A = (+ 7) + (- 7,2)
A = 7 - 7,2
A = - 0,2

B = (-3,4) - (+3,2)

B = - 3,4 - 3,2
B = - 6,6
F = - 7 + 4 = - 3 ; H = - 10 - (5 - 3 + 2) + (13 + 12) = - 10 - (4) + 25 = 11 ; I = 5 - ((12 + 5 - 11) - (7 + 1)) = 5 - ((28) - (8)) = 5 - 20 = - 15
Mercii.mais tu t'es pas tromper au G?
Et le dernier le J= [(4+7)-(11+15)]-[(19+23) - (27+31)] =
J = (4 + 7) - (11 + 15) - (19 + 23) - (27 + 31)) = (11) - (26) - (42) - (58) = 11 - 26 - 42 - 58 = - 115
merci beaucoup
2014-09-23T17:53:25+02:00